SCAI position statement on the performance of percutaneous coronary intervention in ambulatory surgical centers. Issue 4 (2nd July 2020) - Box, Lyndon C.; Blankenship, James C.; Henry, Timothy D.; Messenger, John C.; Cigarroa, Joaquin E.; Moussa, Issam D.; Snyder, Richard W.; Duffy, Peter L.; Carr, Jeffrey G.; Tukaye, Deepali N.; Ang, Lawrence; Shah, Binita; et al.
Abstract: The Centers for Medicare & Medicaid Services (CMS) began reimbursement for percutaneous coronary intervention (PCI) performed in ambulatory surgical centers (ASC) in January 2020. The ability to perform PCI in an ASC has been made possible due to the outcomes data from observational studies and randomized controlled trials supporting same day discharge (SDD) after PCI. In appropriately selected patients for outpatient PCI, clinical outcomes for SDD or routine overnight observation are comparable without any difference in short‐term or long‐term adverse events. Furthermore, a potential for lower cost of care without a compromise in clinical outcomes exists. These studies provide the framework and justification for performing PCI in an ASC. The Society for Cardiovascular Angiography and Interventions (SCAI) supported this coverage decision provided the quality and safety standards for PCI in an ASC were equivalent to the hospital setting. The current position paper is written to provide guidance for starting a PCI program in an ASC with an emphasis on maintaining quality standards. Regulatory requirements and appropriate standards for the facility, staff and physicians are delineated. The consensus document identified appropriate patients for consideration of PCI in an ASC. The key components of an ongoing quality assurance program are defined and the ethical issues relevant to PCI in an ASC are reviewed.